(untitled) (Scientific journal of the Fergana State University, 2025)
This article examines the special knowledge of the teacher, high professional skills, general culture, ideological and moral qualities that solve economic and social problems, as well as the integrated systemic approach of the teacher, active in organizing educational work. The ways of introducing scientifically based methods and tools are discussed.